EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. PERKEBUNAN NUSANTARA V TANDUN TAPUNG HULU - Aris Setiawan; Auzar Ali; Adi Setiawan (STIE Bangkinang Publishing, 2021)
This study aims to determine the effect of motivation on employee performance at PKS PT. Perkebunan Nusantara V Tandun Tapung Hulu. The sample of this study used a technique using the Slovin formula so that the sample in this study were 49 employees of PKS PT. Perkebunan Nusantara V Tandun Tapung Hulu. The data collection techniques used were questionnaires and research files. The data analysis technique used is simple regression analysis with a significant level (α) of 0.05. The results of this study concluded that motivation has a significant effect on employee performance at PKS PT. Perkebunan Nusantara V Tandun Tapung Hulu, with a significant value less than 0.05. The contribution of the independent variable to the dependent variable is strong.